Foundational Numeracy among Rural Elementary School Children : A Case of Birbhum in West Bengal - Chinara, Benudhar; Bagchi, Manjira (JOURNAL OF INDIAN EDUCATION, 2024)
Attainment of numeracy during the foundational stage of school education has remained a priority in India. With this backdrop, the paper examines accomplishment of Grade II specific basic learning outcomes in numeracy as foundational numeracy by IV, VI and VIII graders in rural schools of Birbhum district of West Bengal in India. Responses of 465 children on an arithmetic test indicate that majority of them were not able to recognise the greatest and smallest two-digit numbers, days of the week and month along with months of the year. One-fifth of Grades IV, VI and VIII children on an average could accomplish foundational numeracy poorly, and nearly one-fourth of children could achieve ‘excellent level’ and ‘mastery level’. Foundational numeracy of Grades VI and VIII as well as Grade VIII girls is found significantly higher than Grades VI and VIII boys, respectively. Universal accomplishment of basic foundational numeracy still appears elusive among the rural elementary school children.